Finite Element Model Updating of Large-Span-Cable-Stayed Bridge Based on Response Surface - Yanjun Lv; Juchao Wu; Junlong Li; Wei Wang; Tongning Wang; Ye Yuan; Jianing Wang (Buildings)
Finite element (FE) model updating based on the response surface method using load test data of a cable-stayed bridge. This paper presents a case study of a cable-stayed bridge in which the FE model is refined using the response surface method based on experimental data from dead load and dynamic load tests. The elastic modulus and density of the main girder, tower, and cables are selected as the parameters to be updated, while the mid-span deflection and the first three vertical natural frequencies serve as the responses. The D-optimal experimental design is employed to generate test samples, and F-test analysis is performed to assess the significance of the parameters. The response surface equation is fitted using the least squares method, and the model’s accuracy is subsequently validated. The results show that the discrepancies between the FE model updating, and the experimental data are less than 3% for all responses, indicating a high degree of accuracy. This refined model demonstrates the effectiveness of the response surface method for improving the FE representation of the bridge. It can be applied in the field of damage detection, offering considerable practical value for bridge health monitoring.